Bilateral Serous adenocarcinoma of Ovary coexisting with mature cystic teratoma- Case report and review of literature - Bhagat, Priyanka; Dey, Pranab (Annals of Pathology and Laboratory Medicine, 2015)
Collision tumors represent occurrence of two histologically distinct tumors adjacently in the same organ without any admixture. The simultaneous occurrence of a serous adenocarcinoma with a mature teratoma is very rare. Â In this case report, we describe a rare case of a bilateral serous adenocarcinoma of the ovary with bilateral mature teratoma and serous tubal intraepithelial carcinoma of the fallopian tube.